Bleeding after Endoscopic Resection in Patients with End-Stage Renal Disease on Dialysis: A Multicenter Propensity Score-Matched Analysis - In Kyung Yoo; Chan Gyoo Kim; Young Ju Suh; Younkyung Oh; Gwang Ho Baik; Sun Moon Kim; Young Dae Kim; Chul-Hyun Lim; Jung Won Jeon; Su Jin Hong; Byoung Wook Bang; Joon Sung Kim; et al. (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Frequent bleeding after endoscopic resection (ER) has been reported in patients with end-stage renal disease (ESRD). We aimed to evaluate the association and clinical significance of bleeding with ER in ESRD patients on dialysis. Methods Between February 2008 and December 2018, 7,571 patients, including 47 ESRD patients on dialysis who underwent ER for gastric neoplasia, were enrolled. A total of 47 ESRD patients on dialysis were propensity score-matched 1:10 to 470 non-ESRD patients, to adjust for between-group differences in variables such as age, sex, comorbidities, anticoagulation use, tumor characteristics, and ER method. Matching was performed using an optimal matching algorithm. For the matched data, clustered comparisons were performed using the generalized estimating equation method. Medical records were retrospectively reviewed. Frequency and outcomes of post-ER bleeding were evaluated. Results Bleeding was more frequent in the ESRD with dialysis group than in the non-ESRD group. ESRD with dialysis conferred a significant risk of post-ER bleeding (odds ratio, 6.1; 95% confidence interval, 2.7-13.6; p<0.0001). All post-ER bleeding events were controlled using endoscopic hemostasis except in 1 non-ESRD case that needed surgery. Conclusions ESRD with dialysis confers a bleeding risk after ER. However, all bleeding events could be managed endoscopically without sequelae. Concern about bleeding should not stop endoscopists from performing ER in ESRD patients on dialysis.